The dear enemy effect drives conspecific aggressiveness in an Azteca-Cecropia system - Zorzal, Gabriela; Camarota, Flávio; Dias, Marcondes; Vidal, Diogo M.; Lima, Eraldo; Fregonezi, Aline; Campos, Ricardo I. (Scientific reports, 2021)
Territoriality is costly, and the accurate identification of intruders and the decision to perform aggressive responses are key behavioral traits in social animals. We studied aggression among individuals belonging to close and distant nests of the plant-ant Azteca muelleri , which lives in stems of the pioneer tree Cecropia glaziovii . More specifically, we aim to investigate if the DE (dear-enemy effect—less aggression towards neighbors than strangers) or NN (nasty-neighbor effect—less aggression to strangers than neighbors) effects or even none of them apply for this iconic Azteca-Cecropia system. We further checked if ant aggression towards conspecifics is related to cuticular hydrocarbon profiles (CHCs), which provide chemical cues for nestmate recognition. Therefore, we sampled 46 nests of A . muelleri in three Brazilian Atlantic forest fragments and performed behavioral trials within and between sites. Consistently with the DE effect, we found higher aggression levels in ‘between sites’ versus ‘within sites’ treatments as well as a positive effect of spatial distance on ant aggressiveness. We found no effect of the overall dissimilarities on CHC blend on ant aggressiveness, but of one CHC class, the methylated alkanes. Overall, we provide key insights on nest-mate recognition in obligatory ant-plant mutualisms.